2018
DOI: 10.29202/nvngu/2018-5/4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of material parameters for numerical simulation of the behavior of rocks under true triaxial conditions

Abstract: Purpose. Development a modified model of geomaterials for numerical simulation of the behavior of rocks in a true triaxial stress field. Methodology. The research was conducted on specimens of coal grade "С". Input parameters of materials for basic models in the modeling by the finite element method were taken from the physical experiment. The experiment was conducted on the installation of true triaxial compression. The results of comparative studies on the behavior of rocks in the true triaxial stress field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Te results of laboratory tests show that the failure strain of mudstone is 0.018-0.02, and of the coal is 0.012-0.016 (Figure 3). Tis corresponds with the results of testing soft rock specimens in a volumetric feld [36][37][38] and under uniaxial compression [39,40]. According to the results of tests, it was found that for mudstone, siltstone, argillite, and sandstone with uniaxial strength of 25-40 MPa, the failure criteria for strain is about 0.02-0.03.…”
Section: Simulation Resultssupporting
confidence: 72%
“…Te results of laboratory tests show that the failure strain of mudstone is 0.018-0.02, and of the coal is 0.012-0.016 (Figure 3). Tis corresponds with the results of testing soft rock specimens in a volumetric feld [36][37][38] and under uniaxial compression [39,40]. According to the results of tests, it was found that for mudstone, siltstone, argillite, and sandstone with uniaxial strength of 25-40 MPa, the failure criteria for strain is about 0.02-0.03.…”
Section: Simulation Resultssupporting
confidence: 72%
“…At the same time, the rocks were modeled as heterogeneous. The variation of the physical and mechanical properties of rocks along and across the layering was determined according to the methodology proposed Sakhno et al [29], which is generally consistent with the research of Rzhevsky.…”
Section: Methodsmentioning
confidence: 61%
“…In the numerical simulation model, the thickness of coal seam is 1.5 m. The immediate roof was To simulate the behavior of rocks, a Drucker-Prager deformation model was used. The adequacy of the deformation model was established by simulation experiments [26]. According to the described structure, each layer was assigned a deformation modulus, Poisson's ratio, an angle of internal friction, an adhesion coefficient, and a dilatancy angle (table 1).…”
Section: Methodsmentioning
confidence: 99%